VIDEO DIGITAL WATERMARKING TECHNIQUE AS COPYRIGHT PROTECTION FOR MULTIMEDIA CONTENT DISTRIBUTION - FITRIYANTI LUBIS (NIM 23205302), FETTY
With the rapid growth of multimedia technology and computer networks give simply way to create and distribute the digital content, at the same time emerge illegal copyright protection as a new issue. Because of that reason watermark was introduced as a solution to solve copyright protection for multimedia content. For copyright protection, digital watermark should have these requirements: transparency, the watermark in video content should be invisible or imperceptible. And robust, the watermark should be difficult to remove without degrading the perceived quality of digital content. In this thesis, robustness and transparency can be achieved by embedded watermark in frequency domain. Watermarks are embedded in DC (Direct Current) components of frame. Block modification is performed to embed watermarks to DC (Direct Current) components, based on binary modification Least Significant Bit (LSB) of quantization coefficient DC (Direct Current). All that was implemented in MATLAB 7.0.1. Multi frames extraction show that watermark could extract exactly with video watermark was compressed with quality 25% difference of video without watermark. Watermark robustness supported by implementation of Block Truncation Coding's algorithm to watermark and error correction on watermarking extraction.